On the Subject of Aids: a Study on Qualitative Perceptions and Attitudes of College Students and Lecturers in Chontales, Nicaragua - Cobos-Sanchiz, David (2013)
The aim of this paper is to analyze the perceptions and attitudes in the nicaraguan college community about the HIV/AIDS. This is a qualitative study developed at the National Autonomous University of Nicaragua-Managua, from three focus groups. The procedure for the sample selection was done in a representative way according to the general population of students (n=672) and lecturers (n=89) of the Facultad Autónoma Regional de Chontales (Autonomous Regional Faculty of Chontales). For data analysis, we used the technique of content analysis and qualitative analysis software Atlas.ti, previously creating the system of categories and then the code analysis. At the computer processing of the analysis, we obtained a conceptual network of related codes as a result. The set of conclusions of the study serves to inform and guide future activities of Education and Health Promotion in the context in which research is conducted.